Role of sigma factor RpoS in Cronobacter sakazakii environmental stress tolerance. Issue 1 (1st January 2021) - Zhan, Jie; Qiao, Jun; Wang, Xiaoyuan
ABSTRACT: Cronobacter sakazakii is a food-borne, conditionally pathogenic bacterium that mainly infects neonates, especially premature infants. Previous studies have indicated that an important route of infection for C. sakazakii is through infant formula, suggesting a high stress resistance of the bacterium. RpoS is a σ-factor that is closely related to the bacterial resistance mechanisms. In this study, a C. sakazakii BAA894 model strain was used. An rpoS -deficient mutant strain Δ rpos was constructed using Red homologous recombination, and the differences between the mutant and the wild-type strains were compared. To investigate the functions of the rpoS gene, the membrane formation and cell wall properties of the strains were studied, and the tolerance of each strain to acid, osmotic pressure, desiccation, and drug resistance were compared. The results showed that the membrane formation ability in the mutant strain was increased, auto-aggregation was enhanced, motility, acid resistance and hyperosmotic resistance were alternated to different degrees, and desiccation resistance was stronger than observed in the wild type grown in LB medium but weaker than the wild type cultured in M9 medium. These results showed that rpoS is involved in environmental stress resistance in C. sakazakii BAA894. Finally, transcriptome analysis verified that the deletion of the rpoS gene caused differential expression of resistance-related genes and instigated changes in related metabolic pathways. These messenger RNA results were consistent with the functional experimental results and help explain the phenotypic changes observed in the mutant strain. Graphical abstract: uf0001